Desulfurized flue gas corrosion coupled with deposits in a heating boiler. (February 2018) - Pan, Peiyuan; Chen, Heng; Liang, Zhiyuan; Zhao, Qinxin
Highlights: Corrosion behavior of five steels in the desulfurized flue gas was investigated. High Cl− concentration in the deposits exacerbated the corrosion. As the surface temperature increased, the corrosion of the steels was first exacerbated and then mitigated. The stainless steels performed much better than did the low alloy steel. Abstract: In-plant corrosion tests of five steels were conducted in a heating boiler in China to study the desulfurized flue gas corrosion coupled with deposits after the FGD (flue gas desulfurization) unit. The surface temperature of the steel was the key factor in the deposition and corrosion process. As the surface temperature increased, the corrosion of the steels was first exacerbated due to the increase in the Cl − concentration in the deposits and then mitigated due to the lack of the electrolyte. The stainless steels in this work showed much better performance than did the low alloy steel.